Body composition parameters predict pathological response and outcomes in locally advanced gastric cancer after neoadjuvant treatment: A multicenter, international study. Issue 8 (August 2021) - Lin, Jian-Xian; Tang, Yi-Hui; Zhou, Wen-Xing; Desiderio, Jacopo; Parisi, Amilcare; Xie, Jian-Wei; Wang, Jia-Bin; Cianchi, Fabio; Antonuzzo, Lorenzo; Borghi, Felice; Lu, Jun; Chen, Qi-Yue; et al.
Summary: Background: Body composition profiles influence the prognosis of several types of cancer; however, the role of body composition in patients with locally advanced gastric cancer (LAGC) after neoadjuvant treatment (NT) has not been well characterized. Patients and methods: A total of 213 patients with LAGC who underwent gastrectomy after NT at a high-volume institution from southern China were comprehensively evaluated for primary analysis. Additionally, 170 and 77 patients from Western China and Italy, respectively, were reviewed for external validation. The skeletal muscle index (SMI), skeletal muscle radiodensity (SMD), and the subcutaneous as well as the visceral adiposity index were assessed from clinically acquired CT scans at diagnosis and preoperatively. Results: Overall, none of the body composition parameters significantly changed after NT. The pre-NT skeletal muscle radiodensity (SMD) and change in SMI (ΔSMI) were both significantly lower in the patients with poor response (tumor regression <50%; mean SMD: 43.5 vs 46.5, P = 0.003; mean ΔSMI: −1.0 vs 2.2, P < 0.001), and the cutoff values were calculated according to the Youden index as 43.7 and 1.2, respectively. Based on these 2 parameters, a novel model, the Skeletal Muscle Score (SMS), was proposed to predict the pathological response (AUC = 0.764 alone and = 0.822 in combination with the radiological response). Moreover, patients with an SMI loss >1.2 had a significantly prolonged drainage tube removal time (mean: 10.0 vs 8.2, P = 0.003) and postoperative hospital stay (mean: 11.1 vs 9.8, P = 0.048), as well as a significantly higher rate of postoperative complications (30.9% vs 16.7%, P = 0.015). In the multivariate analysis, SMI loss >1.2 independently predicted poor overall survival (HR: 1.677, 95% CI 1.040–2.704, P = 0.034) and recurrence-free survival (HR: 1.924, 95% CI 1.165–3.175, P = 0.011). ΔSMI was also significantly associated with pathological response, surgical outcomes, and survival in the 2 external cohorts (P all < 0.05). Conclusions: For LAGC, the pre-NT SMD and ΔSMI could accurately predict the pathological response after NT. An SMI loss >1.2 is closely associated with poorer outcomes and may indicate the need more supportive treatment.